Pemenuhan Meaningful Participation Sebagai Standar Konstitusional Good Governance - Agniski Pininta; Arinto Nurcahyono (Wajah Hukum, 2026)
The principle of good governance requires democratic, transparent, and accountable governance, one of the ways to achieve which is through public involvement in public decision-making. In Indonesia, public participation is often still merely formalistic and has not yet resulted in substantial public involvement. Therefore, this article aims to analyze meaningful participation as a constitutional standard in the implementation of good governance. This study employs a normative legal methodology using a legislative, conceptual, and case-specific approach particularly analyzing Constitutional Court rulings regarding public participation in the formation and qualitative- normative analysis of such participation. The findings indicate that meaningful participation has become a constitutional standard demanding the fulfillment of the public’s right to be heard, considered, and provided with explanations regarding their opinions. This standard not only serves as a principle of procedural democracy but also as a tool for testing the constitutionality of the exercise of state power. Thus, strengthening meaningful participation is a primary requirement for realizing good governance that is in harmony with the principles of popular sovereignty and a democratic rule of law, as mandated by the 1945 Constitution.